2020
DOI: 10.1213/ane.0000000000005230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Levobupivacaine Regional Scalp Block on Hemodynamic Stability, Intra- and Postoperative Opioid Consumption in Supratentorial Craniotomies: A Randomized Controlled Trial

Abstract: Background: The anesthetic management of supratentorial craniotomy necessitates tight intraoperative hemodynamic control. This type of surgery may also be associated to substantial postoperative pain. We aimed at evaluating the influence of regional scalp block (SB) on hemodynamic stability during the noxious events of supratentorial craniotomies and total intravenous anesthesia, its influence on intraoperative anesthetic agents' consumption, and its effect on postoperative pain control.Methods: Sixty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 41 publications
3
46
1
1
Order By: Relevance
“…In our study, we found that SNB with 0.2% ropivacaine provided preferable analgesia which relieved postoperative pain for up to 8 h postoperatively. The previous studies showed the persistent analgesic time of SNB on postoperative pain was 4-48 h in adult craniotomy patients (12,15). The reasons for the different duration of SNB on postoperative pain may be related to the type of local anesthetic, the dose of local anesthetic, and the compound application of epinephrine.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In our study, we found that SNB with 0.2% ropivacaine provided preferable analgesia which relieved postoperative pain for up to 8 h postoperatively. The previous studies showed the persistent analgesic time of SNB on postoperative pain was 4-48 h in adult craniotomy patients (12,15). The reasons for the different duration of SNB on postoperative pain may be related to the type of local anesthetic, the dose of local anesthetic, and the compound application of epinephrine.…”
Section: Discussionmentioning
confidence: 98%
“…The theory was that preemptive analgesia prior to surgery can prevent central sensitization caused by noxious stimuli and inflammation ( 19 , 20 ). Previous studies demonstrated that preoperative SNB has beneficial to postoperative pain in adult craniotomy patients ( 12 , 13 ). In our study, we found that SNB with 0.2% ropivacaine provided preferable analgesia which relieved postoperative pain for up to 8 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, scalp block has been proven to be superior over a sham group (with saline) in terms of hemodynamic stability and decreased anesthetic requirement during cranial fixation [55,56]. Scalp block's effect also extends into the postoperative period and has proved to decrease the incidence and severity of postoperative pain [57]. In summary, the incorporation of regional anesthesia has led to a smooth intraoperative course and improved postoperative patient comfort.…”
Section: Regional Anesthesiamentioning
confidence: 99%